Grape stalk valorization for fermentation purposes - Atatoprak, Tuğba (2022)
White and red grape stalks biomass were fractioned to maximize its economic value by the production of fermentable sugars, as other value streams. High yields of extractives and lignin were first obtained, originating a biomass rich in cellulose and hemicellulose, which was subject to acid and enzymatic hydrolysis for production of fermentable sugars. Higher concentrations of sugars were obtained by enzymatic than by dilute acid hydrolysis. These biosugars were used for fermentation processes with Pichia stipitis and Saccharomyces cerevisiae. The presence of higher quantities of xylose favoured P. stipitis to produce higher ethanol yields than S. cerevisiae which is glucose lover. Cellulose nanocrystals were produced from the resulting biomass without monosaccharides. For the first time an integrated valorization of grape stalks followed by an application of one of the valorized streams is presented.